Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2024
DOI: 10.14744/hf.2023.2023.0027
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, determinants, and fibrosis risk stratification of metabolic-associated fatty liver disease in a Turkish primary care setting: A retrospective study

Abstract: Background and Aim: Metabolic-associated fatty liver disease (MAFLD) is a condition that frequently goes unnoticed as it typically remains asymptomatic until progressing to an advanced stage. As a result, it is essential to implement opportunistic screening initiatives within family medicine practices to accurately identify and refer selected at-risk patients to specialized care. This study aims to investigate the prevalence of MAFLD and advanced hepatic fibrosis among primary care patients in Turkiye by utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Postulated to be driven by insulin resistance among other things, 24 the relationship between fatty liver and obesity has been continually reaffirmed 25,26 . Despite the relationship between FPG and NAFLD, diabetes mellitus was not found to be a predictor of steatosis in our patient cohort, which is at variance with that of a Turkish study 27 . This might have to do with the common use of medication such a metformin and pioglitazone among diabetics which are known to affect fatty liver.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Postulated to be driven by insulin resistance among other things, 24 the relationship between fatty liver and obesity has been continually reaffirmed 25,26 . Despite the relationship between FPG and NAFLD, diabetes mellitus was not found to be a predictor of steatosis in our patient cohort, which is at variance with that of a Turkish study 27 . This might have to do with the common use of medication such a metformin and pioglitazone among diabetics which are known to affect fatty liver.…”
Section: Discussionmentioning
confidence: 55%
“…25,26 Despite the relationship between FPG and NAFLD, diabetes mellitus was not found to be a predictor of steatosis in our patient cohort, which is at variance with that of a Turkish study. 27 This might have to do with the common use of medication such a metformin and pioglitazone among diabetics which are known to affect fatty liver. Our work found a significant association between NAFLD and the anthropometric measurements we assessed, which included BMI, WtH and WHtR.…”
Section: Discussionmentioning
confidence: 99%
“…7 Similarly, retrospective studies on patients with NAFLD and metabolic-associated fatty liver disease (MAFLD) have shown that FIB-4 and NFS classify individuals as low risk for advanced fibrosis. 8,9 Furthermore, Thévenot et al investigated noninvasive tests (NITs) for screening advanced liver fibrosis in 189 patients with coronary artery disease and NAFLD. Their findings suggested that NFS or the easy liver fibrosis test (eLIFT) were the most promising first-line biochemical NITs for identifying suitable candidates for Fibroscan.…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective study involving 81 patients with biopsy‐proven advanced fibrosis, the FIB‐4 score and NFS effectively ruled out advanced fibrosis, resulting in a 67% reduction in the necessity for biopsies 7 . Similarly, retrospective studies on patients with NAFLD and metabolic‐associated fatty liver disease (MAFLD) have shown that FIB‐4 and NFS classify individuals as low risk for advanced fibrosis 8,9 …”
Section: Introductionmentioning
confidence: 99%